Pihak Lain dalam diplomasi antarabangsa (Jurnal Bahasa, 2006)
The notion of the Other in current language studies is _frequently juxta-posed against the opposing Self where both entities belong to different sociolinguistic and cultural backgrounds. Here, the latter researched differences are then regularly used as a backdrop to justib the "raison d 'etre" of the varying norms of social, cultural and linguistic behaviour found in the corpus under study to provide the necessary descriptive and explanatory adequacy. Research in the dominion of international diplomacy, however, can suggest an alternate view of the Self and the Other. This paper would like to offer a different view of the Self and the Other in international diplomacy. In this context, the Self and the Other are two sides of the same coin, the Self shaped by his sociolinguistic, cultural and religious identity and the Other, as the same person having to temporarily suspend his Self through subscription to a professional diplomatic culture to achieve the goals of international diplomacy. In this paper, the issue of border crossings to the Other will then be addressed through the exploration of the following two questions. Firstly, what are the aspects of professional diplomatic culture, diplomatic com-munication and disposition that obliges the Self, marked by diversity in religion, ethnicity, politics, history, culture and sociolinguistic norms among members ofdiffering countries to be suspended within the realm of inter-national diplomacy to cross borders to assume the disposition of the Other, concerned with the pursuit of regional and international cooperation? Secondly, how do researched features of diplomatic communication act a bridge between the Self and the Other? The paper ends with the belief that the "la raison de system" in diplomacy will prevail across all other stud-ies in diplomacy, in a place where the Other must dominate over the Self.